Keadilan Substantif dalam Rekrutmen Penyandang Disabilitas: Analisis Dinamika Sistem Merit dan Kebijakan Afirmatif di Polri - Subroto, Rexy Hamza; Rahmi, Annisa; Rahman, Zalfa Ghaffara (Universitas Islam Tribakti Lirboyo Kediri, 2025)
The Indonesian National Police (Polri) has implemented affirmative action policies for persons with disabilities (PWDs) in response to Law No. 8 of 2016, introducing new dynamics into a recruitment system historically characterized by hierarchical structures and physical fitness standards. This study examines the interaction between the merit system and affirmative action in Polri’s recruitment of PWDs, with a particular focus on the realization of substantive justice. Employing a qualitative descriptive-analytical method, this research relies on secondary audiovisual data and literature review, and is theoretically grounded in merit system, recruitment, and affirmative action frameworks. The findings indicate that Polri applies the BETAH principles (Clean, Transparent, Accountable, and Humanist), which are consistent with merit-based recruitment when complemented by reasonable accommodations, including adjusted selection and testing mechanisms, to ensure equal opportunities for PWDs. While this policy reflects a progressive approach, its effectiveness remains contingent upon the development of adaptive technical guidelines and diversified assessment instruments to safeguard objectivity and moral legitimacy in the recruitment process. The study contributes novelty by conceptualizing affirmative action not as a departure from meritocracy, but as a corrective mechanism that addresses the limitations of procedural merit in achieving substantive fairness within inclusive recruitment practices.